Biopsy of sonologically detected peripheral lymph nodes: diagnostic value in HIV positive patients - Gharat, Mayur; Dikshit, Bharat; Pujari, Sanjay; Phalgune, Deepak (International Surgery Journal, 2019)
Background: One of the most common manifestations in human immunodeficiency virus (HIV) is generalized lymphadenopathy. Biopsy of these nodes can help in diagnosing associated conditions. Biopsy of clinically non-palpable lymph nodes can help physician to obtain an early diagnosis of associated diseases in people living with HIV (PLHIV). Present research was undertaken to study diagnostic yield of sonologically detected peripheral lymph node biopsy in symptomatic PLHIV. Methods: One hundred ten PLHIV above age of 18 years referred to surgery department for excision biopsy of sonologically detected peripheral lymph nodes were included. Specimen was sent in normal saline to laboratory for testing and part of the specimen was fixed in formalin for further evaluation. Gram stain, Zeil Nelson stain, histopathological examination and genotype MTBDR plus test were conducted. Comparison of quantitative variables and qualitative variables was done by using Kruskal wallis test and Chi-square test / Fisher’s exact test respectively. Results: Most common diagnosis obtained was tuberculous lymphadenopathy followed by reactive hyperplasia. Significantly higher percentage of patients having weight loss was diagnosed with tuberculous lymphadenopathy. Percentage of tuberculous lymphadenopathy patients was higher in patients who were not on anti-retroviral therapy (ART) as compared to those who were on ART. Median duration of HIV in tuberculosis lymphadenopathy patients was less as compared to patients with malignancy. Sensitivity, and specificity was 91.7%, and 61.5% respectively for diagnostic yield of USG in non-palpable lymph nodes. Conclusions: USG is a sensitive tool for early detection of clinically non-palpable pathological lymph nodes in symptomatic PLHIV.